Chromosomal studies on two endangered catfishes-Ompok bimaculatus (Bloch) and Ompok pabda (Hamilton-Buchanan) - SHARMA, RUPAM (The Indian Journal of Animal Sciences, 2011)
Chromosomal studies are the basic requisite for genetic improvement program and for co~servation of wild gene pool. The catfishes Ompok bimaculatus and Ompok pabda are being endangered due to the habItat destructIo~ and lack of proper management of the stock. For the present karyotypic study on these 2 freshwate:- endangered catfishes, 25 samples of each species were examined and 307 and 330 chromosome spreads of O. blmacul~tus and O. pabda, respectively, were screened. The study revealed the presence of dip~oid chromoson:e ~umber as 42 wl~h the chromosome formula of 12 metacentric, 14 submetacentric and 16 subtelocentnc and telocentnc In both the specIes. The karyotype is characterized by the fundamental arm number (NF) of 68.Â